Asset management for on-chain investment vehicles using DeFi products - Metolkin, Mykyta; Poborský, František; Husák, Martin; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2025)
The thesis explores the use of DeFi products for on-chain asset management and its implications for the financial industry. The paper defines core differences between on-chain and traditional approaches in asset management for investment vehicles and provides suggestions for its improvement. The aspects associated with on-chain fund management are discussed in detail, focusing on the specifics of the asset universe, fund operations and its risks concerning the key elements of the industry.
Vedoucí práce: František Poborský
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: finance [obor bakal. práce]; bakalářské práce; bachelor's theses